Global Finite-Time Output Feedback Stabilization for a Class of Uncertain Nonholonomic Systems - Baojian Du; Fangzheng Gao; Fushun Yuan (Abstract and Applied Analysis)
This paper investigates the problem of global finite-time stabilization by output feedback for a class of nonholonomic systems in chained form with uncertainties. By using backstepping recursive technique and the homogeneous domination approach, a constructive design procedure for output feedback control is given. Together with a novel switching control strategy, the designed controller renders that the states of closed-loop system are regulated to zero in a finite time. A simulation example is provided to illustrate the effectiveness of the proposed approach.